2013
DOI: 10.7567/jjap.52.041201
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of Quantum Dot Formation and Relaxation of InGaAs on GaAs(001)

Abstract: We studied InGaAs quantum dots (QD) formation, the evolutions of QD density, and relaxation as function of indium content and layer thickness on GaAs(001). The results as well as literature show that deposition of InAs after QD formation increases linearly the QD density. This indicates a single constant energy is released per QD. The strain energy at the onset of QD formation and relaxation is constant, i.e., independent of the indium content. Thus relaxation and QD formation can be described better by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Both NWs show hexagonal cores composed of {110} facets and In x Ga 1– x As shells with a thickness of 8–12 nm, less than the nominal value of 18 nm (due to the formation of mounds on the sidewalls and possibly shadowing from neighboring NWs). We note that for In 0.6 Ga 0.4 As growth on planar GaAs(100) the critical thickness is ∼1 nm . Furthermore, in a study of similarly lattice mismatched Si/Ge core–shell NWs, Stranski–Krastanov growth with a wetting layer thickness of 1–2 nm was reported .…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Both NWs show hexagonal cores composed of {110} facets and In x Ga 1– x As shells with a thickness of 8–12 nm, less than the nominal value of 18 nm (due to the formation of mounds on the sidewalls and possibly shadowing from neighboring NWs). We note that for In 0.6 Ga 0.4 As growth on planar GaAs(100) the critical thickness is ∼1 nm . Furthermore, in a study of similarly lattice mismatched Si/Ge core–shell NWs, Stranski–Krastanov growth with a wetting layer thickness of 1–2 nm was reported .…”
mentioning
confidence: 75%
“…We note that for In 0.6 Ga 0.4 As growth on planar GaAs(100) the critical thickness is ∼1 nm. 35 Furthermore, in a study of similarly lattice mismatched Si/Ge core−shell NWs, Stranski− Krastanov growth with a wetting layer thickness of 1−2 nm was reported. 23 For the NW on the left of Figure 3a, two faceted mounds are visible near the corners of the sidewall facets.…”
mentioning
confidence: 99%
“…A notable exception of the merely optical in situ approaches are the first MOVPE in situ STM images that were obtained at GaAs(100) surfaces at temperatures up to 650 °C and at atmospheric pressures . Even though the limited resolution is a drawback compared to STM at ambient or cryogenic temperatures, the in situ STM approach was also used to study quantum dot formation …”
Section: Epitaxial Reference Surfacesmentioning
confidence: 99%
“…Interesting in situ approaches include in situ photoluminescence (PL), which was demonstrated to predict the emission wavelength of InGaN QW‐based light emitting diodes (LEDs) already during growth . Ostwald ripening of InAs quantum dots on GaAs(100) could be observed with in situ STM, and a combined RAS/in situ STM study revealed the dependence of InGaAs quantum dot formation on different surface reconstructions . InGaAs quantum dot formation and island nucleation were studied also by in situ ellipsometry …”
Section: Epitaxial Reference Surfacesmentioning
confidence: 99%
“…However, dislocation nucleation can occur within QDs especially during long InAs growth times. The associated plastic relaxation results in a rapid increase of island size since adding InAs to a more strain-relaxed island costs less strain energy 21 and the dislocated islands become more efficient at capturing monomers. In the present work we term such clusters “large 3D islands” (L3DI) 22 and they may also break the ISD-CZD connection.…”
mentioning
confidence: 99%